O papel da Biópsia Líquida e do DNA celular livre na doença cardiovascular - Uma Revisão Sistemática - Francisco Miguel Marujo Pinheiro (2022)
Background: As Medicine evolves, so do diagnostic procedures, therapies and disease monitoring tools. One of the areas that is under great development is precision medicine. Finding a way to adapt treatments, not only to disease, but also to specific patients is, undoubtedly, a way to make treatments much more successful. Within this topic, liquid biopsy has risen to a state of a very promising technology in the field of oncology. It has shown great potential for diagnostics and monitoring by detecting rising levels of tumor-DNA in the blood way before the disease has imaging proof of progression. Consequently, the hypothesis of applying this technology to other fields is quite legitimate. Alternative and less invasive indicators of cardiovascular disease are important and liquid biopsy can be a powerful option. By analyzing the circulating DNA in the blood, it is possible to investigate specific molecular changes in each patient and use that information to better adjust therapy, evaluate prognostic and risk or even detect early signs of transplant rejection. Material & Methods: This review aimed at systematically investigate if liquid biopsy can be a useful tool to improve medical practice in the clinical setting of myocardial infarction (MI), heart failure (HF) and heart transplantation (HTx). PubMed and Web of Science were searched for studies that reported cfDNA levels in the blood, plasma or urine of adults and/or children and related those levels with MI, HF or HTx. Studies in other language apart from English were excluded, as well as other reviews. Results: From 186 search results, 15 studies were included. The studies reported higher levels of cell-free DNA (cfDNA) in the blood and/or plasma of patients who suffered a myocardial infarction, who had heart failure of an ischemic nature and who registered higher rates of heart transplant rejection. Conclusions: According to the information reported by the included studies, liquid biopsy seems to have several different applications in the field of cardiology. Not only it has shown positive correlation with existing cardiac biomarkers, but also has been proven to be very sensible to therapy adjustments and disease progression. However, further investigation is still warranted since there is a lack of a standard collection and quantification method, as well as larger sample size studies.